Hubungan antara Harga Diri dan Dukungan Sosial dengan Kepercayaan Diri Siswa SMK Nusa Bhakti Semarang - Fitria Rahayu Ningsih; Awalya Awalya (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2020)
This Research can be demonstrated from students who are less active and do not dare to ask during the process of KBM, feel awkward when dealing with many people, unable to respect himself or others, and often compare themselves. The population of this research is all students of VHS Nusa Bhakti Semarang which amounted to 278 students with a sample number of research of 157 students taken with a proportional random sampling technique. The Data Collector tool used in this study is the psychological scale of self-esteem, the psychological scale of social support, and the psychological scale of self-confidence. The results of the first hypothesis analysis show that there is a significant positive relationship between self-esteem and confidence (Î² = 0.416; t = 5,834; p < 0.05), the second hypothesis analysis results in showing that there is a significant positive relationship between social support and student confidence (Î² = 0.364; t = 4,589; p < 0.05), the result of the third hypothesis analysis shows that there is a significant positive relationship between self esteem and social support with student confidence R=0,597,Â F=42,733 > 3,03, p<0,05.Â